2014
DOI: 10.1007/s00726-014-1778-z
|View full text |Cite
|
Sign up to set email alerts
|

Poly-lysine peptidomimetics having potent antimicrobial activity without hemolytic activity

Abstract: Diversity of sequence and structure in naturally occurring antimicrobial peptides (AMPs) limits their intensive structure-activity relationship (SAR) study. In contrast, peptidomimetics have several advantages compared to naturally occurring peptide in terms of simple structure, convenient to analog synthesis, rapid elucidation of optimal physiochemical properties and low-cost synthesis. In search of short antimicrobial peptides using peptidomimetics, which provide facile access to identify the key factors inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…These classes of antimicrobial peptidomimetics are of particular interest owing to the convenient synthesis of the corresponding building blocks and their assembly by using standard solid-phase procedures. Other types of promising antimicrobial peptidomimetics not discussed in the present review comprise arylamide and phenylene ethynylene oligomers [ 125 , 126 , 127 ], small synthetic antimicrobial peptidomimetics (SMAMPs or SAMPs) [ 128 , 129 , 130 ], pyrazole, poly-lysine and histidine-derived ultra-short antimicrobial peptidomimetics [ 131 , 132 , 133 ], macrocyclic peptidomimetics [ 134 ], binaphthyl-based, functionalized oxazoles, biaryl amino acid templates in cyclic β-hairpin cationic antimicrobial peptidomimetics [ 135 ], thiazole peptidomimetics [ 136 ], 1,4-dihydropyridine cationic peptidomimetics [ 137 ], and peptidomimetics containing 3-aminobenzoic acid [ 138 ]. Several such small-molecule mimetics have been reviewed by Ghosh & Haldar [ 139 ].…”
Section: Peptidomimeticsmentioning
confidence: 99%
“…These classes of antimicrobial peptidomimetics are of particular interest owing to the convenient synthesis of the corresponding building blocks and their assembly by using standard solid-phase procedures. Other types of promising antimicrobial peptidomimetics not discussed in the present review comprise arylamide and phenylene ethynylene oligomers [ 125 , 126 , 127 ], small synthetic antimicrobial peptidomimetics (SMAMPs or SAMPs) [ 128 , 129 , 130 ], pyrazole, poly-lysine and histidine-derived ultra-short antimicrobial peptidomimetics [ 131 , 132 , 133 ], macrocyclic peptidomimetics [ 134 ], binaphthyl-based, functionalized oxazoles, biaryl amino acid templates in cyclic β-hairpin cationic antimicrobial peptidomimetics [ 135 ], thiazole peptidomimetics [ 136 ], 1,4-dihydropyridine cationic peptidomimetics [ 137 ], and peptidomimetics containing 3-aminobenzoic acid [ 138 ]. Several such small-molecule mimetics have been reviewed by Ghosh & Haldar [ 139 ].…”
Section: Peptidomimeticsmentioning
confidence: 99%
“…To exemplify, they recently designed a novel cyclic lipopeptides (cyclo-[ D -Ala-(12-guanidino-dodecanoyl)Thr-D-Val-Val-DaThr-D-Asn]) ( Figure 6 ) derived from fusaricidin, which proved to inhibit both growth of S. aureus biofilms in vitro and proliferation of S. aureus in vivo [ 271 ]. By using combinations of hydrocarbon tails and other hydrophobic moieties in conjugation with polylysine and lysine analogues, Ahn et al [ 272 ] have demonstrated successful design of very simple antimicrobial peptides, with no detectable hemolytic activity [ 272 ]. Though their precise mode of action still needs to be characterized, they present convincing data demonstrating that the peptides work through different mechanisms than the classical membrane targeting peptides like melittin [ 272 ].…”
Section: Peptidomimetics For Antimicrobial Researchmentioning
confidence: 99%
“…By using combinations of hydrocarbon tails and other hydrophobic moieties in conjugation with polylysine and lysine analogues, Ahn et al [ 272 ] have demonstrated successful design of very simple antimicrobial peptides, with no detectable hemolytic activity [ 272 ]. Though their precise mode of action still needs to be characterized, they present convincing data demonstrating that the peptides work through different mechanisms than the classical membrane targeting peptides like melittin [ 272 ].…”
Section: Peptidomimetics For Antimicrobial Researchmentioning
confidence: 99%
“…When AMPs have been applied in attempt to combat MRSA there have been numerous promising findings reported ( Table 2 , with in-depth AMP reviews available by [ 85 , 87 , 88 ]). However, in their native state, AMPs have been limited in their development due to their poor stability and activity at physiological conditions coupled with their vulnerability to protease degradation, potential immunogenicity, and cytotoxicity to red blood cells [ 89 , 90 ]. To address this, AMPs are now being developed with modified peptide sequences to enhance activity [ 84 , 91 , 92 ] or are being synthesized as pro-drugs or “peptidomimetics” to avoid toxicity issues, enhance retention, and allow for improved efficacy at the site of action.…”
Section: Emerging Therapeutic Agents Used In Nanomedicines To Treamentioning
confidence: 99%
“…To address this, AMPs are now being developed with modified peptide sequences to enhance activity [ 84 , 91 , 92 ] or are being synthesized as pro-drugs or “peptidomimetics” to avoid toxicity issues, enhance retention, and allow for improved efficacy at the site of action. Several strategies exist to achieve this, including modifying the carbon chain length and functional group [ 90 ], PEGylation, net charge reduction [ 93 ], nanoparticle or antibody conjugation [ 94 , 95 ], and synergistic delivery with or antibiotics [ 96 ].…”
Section: Emerging Therapeutic Agents Used In Nanomedicines To Treamentioning
confidence: 99%